WEDGE: an anticoagulant thrombin mutant produced by autoactivation. (29th November 2014) - Wood, D. C.; Pelc, L. A.; Pozzi, N.; Wallisch, M.; Verbout, N. G.; Tucker, E. I.; Gruber, A.; Di Cera, E.
Summary Background The production of therapeutically relevant proteases typically involves activation of a zymogen precursor by external enzymes, which may raise regulatory issues about availability and purity. Recent studies of thrombin precursors have shown how to engineer constructs that spontaneously convert to the mature protease by autoactivation, without the need for external enzymes. Objectives Autoactivation is an innovative strategy that promises to simplify the production of proteases of therapeutic relevance, but has not been tested in practical applications. The aim of this study was to provide a direct test of this strategy. Methods An autoactivating version of the thrombin mutant W215A/E217A (WE), which is currently in preclinical development as an anticoagulant, was engineered. Results and Conclusions The autoactivating version of WE can be produced in large quantities, like WE made in BHK cells or Escherichia coli, and retains all significant functional properties in vitro and in vivo. The results serve as proof of principle that autoactivation is an innovative and effective strategy for the production of trypsin‐like proteases of therapeutic relevance.